1992
DOI: 10.1161/01.str.23.10.1446
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia in patients with cerebrovascular lesions. A study of causative factors.

Abstract: Background and Purpose: Psychological and biological hypotheses have been proposed to explain anosognosia. We correlated the presence of anosognosia with the presence and severity of psychiatric disturbances, neglect, intellectual impairments, and computed tomographic evidence of lesion size, location, and measurements of brain atrophy.Methods: A series of 80 patients with acute stroke were assessed using a battery of psychiatric and neuropsychological tests and computed tomography.Results: There were five mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(121 citation statements)
references
References 26 publications
9
109
0
3
Order By: Relevance
“…First, the cognitive disturbances found in subjects with NϩA pertain to A itself. 3,24,25 In fact, Jehkonen et al 24 found that patients with A had poorer orientation and verbal memory, and Feinberg et al 3 observed verbal confabulation in subjects with A. Starkstein et al 25 found significantly higher frequencies of hemispatial neglect and related phenomena, as well as deficits in recognizing facial emotions and in receptive prosody in patients with A. Second, in our study we wanted to take more into consideration the motor FIM score, which assesses self-sufficiency in the activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…First, the cognitive disturbances found in subjects with NϩA pertain to A itself. 3,24,25 In fact, Jehkonen et al 24 found that patients with A had poorer orientation and verbal memory, and Feinberg et al 3 observed verbal confabulation in subjects with A. Starkstein et al 25 found significantly higher frequencies of hemispatial neglect and related phenomena, as well as deficits in recognizing facial emotions and in receptive prosody in patients with A. Second, in our study we wanted to take more into consideration the motor FIM score, which assesses self-sufficiency in the activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Second, PSD has been observed in individuals with anosognosia. 16 Third, late-onset depression has been associated with white matter disease and small silent infarcts. 12,17,18 Fourth, poststroke depressive-like symptoms have been noted in several animal models.…”
Section: February 2017mentioning
confidence: 99%
“…22,26,38,39 Reding et al 26 also indicated using participants' gestures as responses. A noncompletion rate of 14 from at least 46 attempts was achieved (based on 3 studies that reported numbers of individuals with aphasia that did not complete 26,38,39 and 2 studies that reported the number that did.…”
Section: Modified Questions or Responses Requiredmentioning
confidence: 99%
“…22,26,38,39 Reding et al 26 also indicated using participants' gestures as responses. A noncompletion rate of 14 from at least 46 attempts was achieved (based on 3 studies that reported numbers of individuals with aphasia that did not complete 26,38,39 and 2 studies that reported the number that did. 38,39 Two studies 22,40 (both with 'limited' aphasia) reported using response cards as a supplementary method: as part of the interview assessment with the SADBD 22 ; and to aid administration of the SDS questionnaire.…”
Section: Modified Questions or Responses Requiredmentioning
confidence: 99%